1973
DOI: 10.1038/sc.1973.2
|View full text |Cite
|
Sign up to set email alerts
|

The circulatory behaviour in complete chronic paraplegia

Abstract: DURING World War II the systematic study of the circulatory problems in para plegia was began by Sir Ludwig Guttmann and continued after the war by him and his colleagues at Stoke Mandeville. The loss of thermoregulatory vasomotor adaptation (Cooper et al., 1957; Guttmann et al., 1958) and the cardiovascular responses to bladder distension (Guttmann & Whitteridge, 1947; Cunningham et al., 1953), were the main results of the first studies. In the following years, studies were made on the behaviour of denervated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1980
1980
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…It has been found that in spinal cord injured (SCI) individuals the function of the muscle pump and the sympathetic nervous system are severely disturbed, causing an impaired ability to redistribute blood (Biart and Maury 1973;Kinzer and Convertino 1989;Furher 1990). It has been shown that this contributes to cardiovascular intolerance during orthostatic challenges and exercise or strenuous activities in daily life (Gass and Camp 1984;Figoni 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that in spinal cord injured (SCI) individuals the function of the muscle pump and the sympathetic nervous system are severely disturbed, causing an impaired ability to redistribute blood (Biart and Maury 1973;Kinzer and Convertino 1989;Furher 1990). It has been shown that this contributes to cardiovascular intolerance during orthostatic challenges and exercise or strenuous activities in daily life (Gass and Camp 1984;Figoni 1993).…”
Section: Introductionmentioning
confidence: 99%
“…4,15 The failure of the sympathetic nervous system to protect the circulation against gravity in these patients is evidenced by reduced levels of catecholamines and loss of vasomotor adjustments. 1,7,16,17 A further response to PH is the activation of the reninangiotensin-aldosterone system (RAS), in an attempt to preserve renal blood¯ow by sodium retention, extracellular volume expansion, and possibly increasing mean arterial pressure. 18 ± 20 To the extent that aerents from the sympathetic nervous system are involved in RAS activation, disruption of the sympathetic nervous system may result in inadequate responsiveness by the RAS to the reduction in renal blood and an incomplete compensation for PH.…”
Section: Discussionmentioning
confidence: 99%
“…Except in those individuals when tilting triggers o strong spasms which help the venous return, 29 tilting upwards usually causes a more unpleasant OH than does the change to a sitting position probably due to the fact that the internal organs are more compressed and that a person who is tetraplegic can lean forwards somewhat when sitting.…”
Section: Oh and Changes Of Positionmentioning
confidence: 99%